Gas chromatography/mass spectrometry analysis of some aldehydes in cooking-oil smoke condensate and their formation mechanism - WANG Kai-xiong; ZHU Xing-dong; WU Ping-gu (浙江大学学报. 农业与生命科学版)
The components of aldehydes and their relative quantities in cooking-oil smoke condensate were analyzed by gas chromatography/mass spectrometry. Five aldehydes, i. e. nonanal, 2-heptenal, 2-decenal, 2, 4-decedienal, 9, 17-octadecadienal, were found in the sample collected from the restaurant, and the peak area of aldehydes was 12.65 percent of total peak area. Meanwhile the sample collected from resident house was determined and thirteen aldehydes including hexanal, heptanal, octanal, nonanal, 2-octenal, 2-undecenal, 9, 17-octadecadienal, 2-octyl-cyclopropaneoctanal were identified, and the peak area of aldehydes was 15.20 percent of total peak area. The formation mechanism of the aldehydes was also discussed.